Community health care integration and fiscal expenditures: evidence from a synthetic control approach - Xiang, Yi; Zhong, Guangjing; Lei, Xiaofeng; Liu, Longqing (Frontiers in Public Health, 2025)
BackgroundDoes the implementation of community healthcare integration policies affect fiscal expenditures as a key measure in addressing older healthcare demands and promoting healthy aging?MethodsThis study utilizes the implementation of community healthcare integration in Yantai, a prefecture-level city in China, as a natural experiment to analyze its fiscal expenditure consequences by using the synthetic control approach.ResultsOur empirical findings indicate that the program implementation markedly decreased fiscal expenditures in pilot cities. The decrease in expenditure is solely due to policy execution, with no confounding variables detected. The program implementation negatively impacted fiscal expenditures mainly by decreasing government healthcare spending in pilot zones.ConclusionConsequently, in the ongoing effort to enhance community healthcare integration, local governments must devise context-tailored implementation strategies to attain sustainable growth, alleviate fiscal burdens, and improve older adult care services.